Designing Stock Taking Policy For Reducing Total Cost Of Stock Take Using Cycle Counting Method In Raw Material Distribution Center Of Pt Xyz - Michael Panjaitan; Ari Yanuar Ridwan; Budi Santosa (eProceedings of Engineering, 2015)
PT XYZ is a company that engaged in logistics. It holds inventories of raw materials of PT ABC. PT XYZ has warehouse which the value of raw material inventory accuracy is 86.41% out of the target set at 99.95%. The type of goods in warehouse classified into two types namely, packaging and raw materials. Observed from the investment value, raw materials has contributed 97.04%, while 2.96% of packaging material. PT XYZ has 16 SKUs raw material. Activity stock take existing spending Rp, 35.566.500,-. Stock take cost is expensive accompanied by the performance of the accuracy of warehouse is relatively distant from target achievement. PT XYZ requires a stock take design policy proposals aim to reducing costs and maintaining the accuracy of the goods at warehouse. Along with the stock take optimal policy can help reduce the stock take cost. Based on the calculation and analysis, implementation of policy proposals stock take can reduce processing time stock take activity, reducing the number of SKUs are calculated each stock take of its activities. Stock take of the proposed activity may minimizing costs up to Rp.15.208.500. Business process activities stock take activity stock increased by 1.67%. In terms, stock take of the proposed activity is able to minimize the cycle time per second 161.67 per pallet. Keywords: 3PL, Inventory Record Accuracy, Cycle Counting, Cost Stock Take, Stock Take Activity